Parent's perception on face-to-face learning - Latasha Safira (Center for Indonesian Policy Studies (CIPS), 2022)
Throughout Indonesia, parental engagement with schools has mostly been through their involvement in their children's education. This parental involvement increased during distance learning brought by the Covid-19 pandemic, as parents needed to supervise their children's studies, monitor their academic progress, ensure the completion of assignments, and maintain communication with teachers. However, parental involvement in school management and the decision-making process has remained low, despite the Ministry of Education, Culture, Research and Technology (MOECRT) mandating the formation of School Committees to support school management, as well as increase transparency and accountability.
Keywords: 330